2008
DOI: 10.1097/shk.0b013e318070c8b9
|View full text |Cite
|
Sign up to set email alerts
|

Cd4+ T-Cell Depletion Is Not Associated With Alterations in Survival, Bacterial Clearance, and Inflammation After Cecal Ligation and Puncture

Abstract: Our recent studies indicate that mice depleted of T cells that bear the alphabeta T-cell receptor (alphabeta T cells) show less inflammation, less physiological dysfunction, and improved survival after cecal ligation and puncture (CLP) compared with control mice. Classic CD4(+) and CD8(+) T cells comprise most of the alphabeta T-cell population. We previously showed that CD8(+) T cells, in conjunction with natural killer (NK) cells, participate in CLP-induced inflammation. However, the contribution of CD4(+) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…The role of CD4 ϩ lymphocytes on sepsis-induced mortality is not entirely clear. Two recent studies examining this issue have come to different conclusions, demonstrating that depletion of this cell type either has no effect (38) or is associated with increased mortality in CLP (39). However, the first study used a model with rapid 100% lethality, and neither examined the intestine, making them difficult to compare to our results.…”
Section: Discussioncontrasting
confidence: 57%
“…The role of CD4 ϩ lymphocytes on sepsis-induced mortality is not entirely clear. Two recent studies examining this issue have come to different conclusions, demonstrating that depletion of this cell type either has no effect (38) or is associated with increased mortality in CLP (39). However, the first study used a model with rapid 100% lethality, and neither examined the intestine, making them difficult to compare to our results.…”
Section: Discussioncontrasting
confidence: 57%
“…Previously published reports that studied CD4+ T cell responses during sepsis have focused primarily on either the acute phase of septic shock[17, 18, 43] or on dysfunction proximal in time to the initial insult[9, 50-52]. Little is understood about CD4+ T cell dysfunction following severe sepsis and its impact on sepsis-induced immunosuppression in both mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…The viewpoints on the control of innate immune cells by the adaptive immune system during sepsis remain controversial (14)(15)(16)(17)(18). Research using mouse models of sepsis induced by cecal ligation and puncture (CLP) (19) produced different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Research using mouse models of sepsis induced by cecal ligation and puncture (CLP) (19) produced different conclusions. Enoh et al (15) showed that CD4 + T-cell depletion is not associated with alternations in survival, bacterial clearance and inflammation of mice with CLP-induced sepsis. Reim et al (17) showed that T cells contribute both to activation of innate immune cells and to amplification of the immune response against invading pathogens in mice with CLP-induced sepsis, and other septic models have yielded different viewpoints.…”
Section: Discussionmentioning
confidence: 99%